Update on the safety profile of certolizumab pegol in rheumatoid arthritis: an integrated analysis from clinical trials - Bykerk, V P (Ann Rheum Dis, 2015)
OBJECTIVE: To report the long-term safety data of certolizumab pegol (CZP) in rheumatoid arthritis (RA) accumulated as of 30 November 2011. DESIGN: Data from 10 completed randomised controlled trials (RCT) of CZP in RA and several open-label extensions (OLE) were pooled across all doses. Reported adverse events (AE) occurred between the first dose and 84 days after the last dose. All deaths, serious infectious events (SIE) and malignancies were reviewed by external experts, classified according to predefined rules, and validated by an external steering committee. Incidence rates (IR) and event rates (ER) per 100 patient-years (PY) are presented. RESULTS: 4049 RA patients who received CZP were included in the safety pooling; total exposure 9277 PY, mean exposure 2.1 years (range 0.04–7.6). SIE, most frequently pneumonia (IR 0.73/100 PY), were the most common serious AE, occurring more frequently in CZP compared to placebo-treated patients in RCT (IR 5.61/100 PY vs 1.35/100 PY, odds ratio (OR) 4.35, 95% CI 0.65 to 29.30). SIE rates were lower in the CZP-treated population including OLE (ER 4.33/100 PY). 44 patients developed tuberculosis (IR 0.47/100 PY), 39 from high endemic regions. 58 deaths occurred in CZP-exposed patients (IR 0.63/100 PY) and 70 developed malignancies excluding non-melanoma skin cancer (IR 0.76/100 PY), including five lymphomas (IR 0.05/100 PY). CONCLUSIONS: No new or unexpected safety signals associated with CZP emerged in this updated long-term safety analysis. While SIE rates were higher for CZP than for placebo in RCT, the rate decreased with continued exposure to CZP. These rates are consistent with data previously reported for CZP and other tumour necrosis factor inhibitors.